2019
DOI: 10.1111/hsc.12718
|View full text |Cite
|
Sign up to set email alerts
|

“They’re always in a hurry” – Older people´s perceptions of access and recognition in health and social care services

Abstract: The article examines older people's perceptions of quality of life from the perspective of access and use of health and social care services. The data include focus group discussions with older people living alone. The data were analysed using thematic analysis focusing on the older people's collective views on health and social care services as supportive or restrictive factors for their quality of life. Two central themes were present in all the focus group discussions: the importance of accessing services a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 17 publications
1
41
0
3
Order By: Relevance
“…While most of these people had to deal with physical and mental deteriorations such as diminished vision and, consequently, restrictions such as loss of mobility, they focused on the remaining options available to them-they wanted to enjoy their lives despite their old age (Behm et al 2013;Bjornsdottir 2018;Faeo et al 2020;Moe et al 2013;Spoorenberg et al 2015). The primary studies showed that older people wanted to be seen and accepted as valuable individuals who still act on their own, take pleasure in daily activities and contribute something to society (Behm et al 2013;Krothe 1992;Martin-Matthews and Sims-Gould 2008;Moe et al 2013;Tiilikainen et al 2019;Toien et al 2015). This was described as being "confirmed […] as a human being" (Moe et al 2013, p. 744) and "a wish for dignity, value, and selfesteem" (Toien et al 2015), p. 706).…”
Section: Feeling Like a Meaningful Human Beingmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of these people had to deal with physical and mental deteriorations such as diminished vision and, consequently, restrictions such as loss of mobility, they focused on the remaining options available to them-they wanted to enjoy their lives despite their old age (Behm et al 2013;Bjornsdottir 2018;Faeo et al 2020;Moe et al 2013;Spoorenberg et al 2015). The primary studies showed that older people wanted to be seen and accepted as valuable individuals who still act on their own, take pleasure in daily activities and contribute something to society (Behm et al 2013;Krothe 1992;Martin-Matthews and Sims-Gould 2008;Moe et al 2013;Tiilikainen et al 2019;Toien et al 2015). This was described as being "confirmed […] as a human being" (Moe et al 2013, p. 744) and "a wish for dignity, value, and selfesteem" (Toien et al 2015), p. 706).…”
Section: Feeling Like a Meaningful Human Beingmentioning
confidence: 99%
“…In view of this, it was not surprising that whether an older person felt like a meaningful human being was strongly connected to their care relationships. The most important aspect of this was social contact itself, i.e., conversations and interest toward the older people (Behm et al 2013;Jarling et al 2018;Krothe 1992;Moe et al 2013;Soodeen et al 2007;Tiilikainen et al 2019). Soodeen et al (2007) summarized:…”
Section: Feeling Like a Meaningful Human Beingmentioning
confidence: 99%
“…Other studies found autonomy in decision-making is important to older adults and is related to perceived quality of life, and meaningful social engagement and community participation are significant contributors to successful aging (Tiilikainen et al, 2019). Individual and group empowerment can be enhanced through community group engagement (Fisher & Gosselink, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, the hurried nature of formal care interactions leaves few opportunities to develop these relationships with increasingly limited time apportioned to each service user. Findings from interviews with older people in Finland suggest that the busyness of care workers and short time slots extends across borders (38) .…”
Section: Discussionmentioning
confidence: 99%